Functional anatomy - Kent, Peter; Seery, Paul.; Trikojus, Tom. (Bendigo, Vic. : Video Education Australasia, 2009)
Examines how our anatomy enables us to be physically active. The topic has been split into four body systems; skeletal system, muscular system, respiratory system, and circulatory system. Uses extensive graphics and sporting footage. Provides a comprehensive overview of functional anatomy.
Voice-over, Peter Kent; writer/producer/director, Tom Trikojus; program teacher notes, Paul Seery
Keywords: Exercise -- Physiological aspects; Human anatomy; Human mechanics; Sports -- Physiological aspects